2012
DOI: 10.1111/j.1440-1843.2012.02230.x
|View full text |Cite
|
Sign up to set email alerts
|

Is chest tube insertion with ultrasound guidance safe in patients using clopidogrel?

Abstract: Given the known effects of clopidogrel on platelet function, these results were interpreted as indicating that clopidogrel therapy is a relative but not an absolute contraindication to chest tube insertion, if an experienced operator places a small-bore tube under ultrasound guidance.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
8
0
1

Year Published

2015
2015
2022
2022

Publication Types

Select...
7
2

Relationship

0
9

Authors

Journals

citations
Cited by 22 publications
(9 citation statements)
references
References 13 publications
0
8
0
1
Order By: Relevance
“…The retrospective data on pleural drainage and clopidogrel encompass a total of 54 patients across two studies who underwent 67 US-guided small-bore chest tube insertions (53,54). No life-threatening bleeding was reported in any of these procedures.…”
Section: Percutaneous Pleural Procedures and Clopidogrelmentioning
confidence: 99%
“…The retrospective data on pleural drainage and clopidogrel encompass a total of 54 patients across two studies who underwent 67 US-guided small-bore chest tube insertions (53,54). No life-threatening bleeding was reported in any of these procedures.…”
Section: Percutaneous Pleural Procedures and Clopidogrelmentioning
confidence: 99%
“…Cette opinion concorde avec les données de la littérature qui rapportent une incidence des complications hémorra-giques après drainage thoracique chez des patients sans AAP entre 0 et 4,2 % [11][12][13][14][15][16][17][18][19][33][34][35][36][37]. Une étude prospective monocentrique a rapporté l'absence de complication hémorragique au cours de 24 drainages thoraciques réalisés sous clopidogrel [38]. Dans notre étude, les pneumologues exprimaient peu de réticence à effectuer un drainage thoracique sous aspirine contrairement au clopidogrel.…”
Section: Drainage Thoraciqueunclassified
“…It has been a controversial topic of whether clopidogrel is associated with significant bleeding risk in patients undergoing simple noninvasive procedures. Literature over the past 15 years was supportive of performing small-bore (<14 Fr), ultrasound-guided thoracocentesis while patients are on clopidogrel [1][2][3][4][5]. On the other hand, several studies published recently found a significant risk of bleeding from performing these procedures on such patients.…”
Section: Introductionmentioning
confidence: 99%